Quantitative and Qualitative Phytochemical Analysis of Manilkara zapota (Sapodilla) Extract and Its Antibacterial Activity on Some Gram-Positive and Gram-Negative Bacteria - Shahla Hashemi Shahraki; Fereshteh Mohamadhasani Javar; Mehdi Rahimi (Scientifica, 2023)
A molecule’s antibacterial and antiviral action is exclusively linked to substances that selectively eradicate bacteria and viruses or inhibit their growth without significantly damaging adjacent tissues. The purpose of this research is to evaluate quantitative and qualitative phytochemical analysis and the antibacterial effects of Manilkara zapota fruit extract on some Gram-positive (Staphylococcus aureus, Enterococcus faecalis, Micrococcus luteus, Bacillus cereus, and Listeria monocytogenes) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae) bacteria in laboratory conditions. Qualitative chemical screening was used to identify different classes of active chemical compounds, and quantitative analysis of the chemical composition of the plant was used to measure the contents of flavonoid, total phenol, anthocyanin, and antioxidant activity. Antibacterial effects of Manilkara zapota ethanol extract were determined by disk diffusion methods, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC). Qualitative chemical screening revealed the presence of flavonoids, tannins, quinones, terpenoids, and glycosides while the presence of saponins was not observed. The bacterial inhibition zones against Listeria monocytogenes, Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus, Micrococcus luteus, Escherichia coli, Klebsiella pneumoniae, and Bacillus cereus are 15.44 ± 0.33, 12.23 ± 0.11, 8.85 ± 0.2, 14.22 ± 0.33, 15 ± 0.44, 9.33 ± 0.13, 10.33 ± 0.36 and 14.55 ± 0.45 mm, respectively. MIC and MBC of the extract in Gram-positive bacteria were 25 and 50, and in Gram-negative bacteria were 50 and 100 mg/ml, respectively. The findings imply that Manilkara zapota extract includes a good amount of plant compounds and can be a significant source for a variety of uses, including antibacterial.